2016
DOI: 10.1515/agriceng-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Odour Emission from Piggery through Application of Heat Recovery System

Abstract: The aim of the study was to determine the effect of manure cooling by the use of the heat recovery system on odour emission from a deep litter piggery. Annual comparative research was carried out in a twin-room deep litter piggery located in Wielkopolska Voivodeship. The recovered heat was transferred to central heating and domestic hot water systems of a residential building. The study showed that the average odour emission rate from the room, where heat was recovered (0.192±0.083 ouE·s−1·kg m.c.−1) was lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…It was from 5.76 ou E • (s • pig) -1 to 46.79 ou E • (s • pig) -1 and mean value equalled to 20.93 ou E • (s • pig) -1 ( Table 3). This value is similar to results of measurements conducted in commercial deep-litter piggeries by Rzeznik et al [19]. The mean odour emission factor for finishers was 16.93 ou E • (s • pig) -1 .…”
Section: Odour Emission Factorsupporting
confidence: 90%
See 1 more Smart Citation
“…It was from 5.76 ou E • (s • pig) -1 to 46.79 ou E • (s • pig) -1 and mean value equalled to 20.93 ou E • (s • pig) -1 ( Table 3). This value is similar to results of measurements conducted in commercial deep-litter piggeries by Rzeznik et al [19]. The mean odour emission factor for finishers was 16.93 ou E • (s • pig) -1 .…”
Section: Odour Emission Factorsupporting
confidence: 90%
“…Wang et al [18] conducted study in experimental room and noted mean odour concentration -67.5 ou E • m -3 . Rzeznik et al [19] measured odour concentration in commercial deep-litter piggery. The mean value was 413 ou E • m -3 .…”
Section: Odour Concentrationmentioning
confidence: 99%
“…The published odor emission factors from deep-litter piggery are lower than results of this study. Rzeźnik et al (2014) recorded values ranging from 0.06 to 0.20 ou E •s -1 •kg b.m. -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Only Wi et al (2019) determined a much higher factor, comparable to the results of this work, amounting to 3.12-16.56 g•day -1 •pig -1 .The momentary ventilation rate was constant and it was 4.42 m -3 •s -1 . The odor concentration in the studied fattening house ranged from 755 to 11775 ou E •m -3 and was diversified (coefficient of variation 43.8%) Rzeźnik et al (2014),. during research carried out in production buildings on deep litter, observed odor concentration values ranging from 137 to 1247 ou E •m -3 .…”
mentioning
confidence: 96%